Spain & Portugal's best trips 32 amazing road trips - St Louis, Regis; Butler, Stuart; Christiani, Kerry; Ham, Anthony; Noble,Isabella; Noble,John; Quintero, Josephine; Sainsbury, Brendan; Symington, Andy (Footscray, Victoria, Australia Lonely Planet Publications Pty Limited, 2016)
Discover the freedom of open roads while touring Spain and Portugal with Lonely Planet Spain and Portugal's Best Trips, your passport to up-to-date advice on uniquely encountering Spain and Portugal via el auto. Get to Spain and Portugal, rent a car and hit the road!
Plan your trip. Welcome to Spain & Portugal -- Spain & Portugal classic trips -- Spain & Portugal highlights -- If you like -- Need to know -- City guide -- Spain & Portugal by region -- On the road. Madrid & Central Spain -- Northern Spain & Basque Country -- Barcelona & Eastern Spain -- Andalucía & Southern Spain -- Portugal -- Road trip essentials.
At head of title: Lonely Planet.
Extra pull-out map.
Includes index.
Keywords: Travel guides; Spain -- Guidebooks; Portugal -- Guidebooks